Lack of support in medical device regulation within academia - Hendricusdottir, R; Hussain, A; Milnthorpe, W; Bergmann, J (MDPI, 2021)

(untitled)
New medical technologies can transform healthcare, and automation of processes is becoming increasingly ubiquitous within the patient care sector. Many innovative ideas arise from academia, but regulations need to be taken into account if they want to reach the market and create a real impact. This is particularly relevant for applied fields, such as prosthetics, which continuously generates cutting-edge solutions. However, it remains unclear how well the regulatory pathway is supported within universities. This study applied a data-driven assessment of available online information regarding support of medical device regulations within universities. A total of 109,200 URLs were screened for regulatory information associated with universities in the UK and the USA. The results show that based on available online data, 55% of the selected universities in the UK and 35% in the USA did not provide any support for medical device regulations. There is a big discrepancy between universities in terms of the available support, as well as the kind of information that is made accessible by the academic institutes. It is suggested that increasing support for regulatory strategies during the early phases of research and development will likely yield a better translation of technologies into clinical care. Universities can play a more active role in this.